Análisis de crecimiento de rúgula (Eruca sativa Mill.) en la Sabana de Bogotá, bajo dos condiciones ambientales (2010)
Arugula is a horticultural species that has provoked interest as a gourmet product, being the edible portions the fresh young leaves. The development of its production technology, the knowledge of its growth and development for tropical conditions are lacking. According to these aspects, the following objectives were proposed: establishment of the growth indices, the leaf area, the fresh and dry weight; determination of growth rates for both environments: relative growth rate, rate of crop growth, net assimilation rate, leaf area index; ascertainment of growth curves and the mathematical equations that best fit the relationship between growth rates and environmental conditions. 972 plants of Eruca sativa Mill. were placed under greenhouse and free exposure conditions, during two cultivation cycles, during the second term of 2006 at the U.D.C.A,s Teaching-Research area. For the growth indices data, each 15 days destructive samples were taken from plants in complete competition; equally, to obtain information on the growth rates, continuous samples were obtained. Environmental information was captured to construct the mathematical equations. The collected information to determine possible differences in the growth variables was submitted to a “t” test, using SAS. The results showed a better performance of arugula under greenhouse conditions, since the main achieved growth rates were enhanced. Environmental conditions had a major influence on plant growth. Greenhouse conditions are recommended for planting arugula, since they represent optimal growth conditions.